Needs Analysis for Developing Exposition Writing Materials Using the DTMT Method for Senior High School Students - Wulandari, Indah Astutik; Nurhadi, Nurhadi; Roekhan, Roekhan (AL-ISHLAH: Jurnal Pendidikan, 2024)
Teaching materials that suit students' needs can help them increase their motivation to learn. These teaching materials can also be developed using appropriate methods by considering the learning objectives and skills. One of the methods that can be used in learning to write is the DTMT method. The DTMT method, which stand for (Dari Teks Menuju Teks or From Text to Text) is used to support the structured development of writing skills. In the early stages of product development, it is necessary to conduct a needs analysis to support the development of teaching materials for writing exposition texts using the DTMT method. The needs analysis in this study is part of the development research with the ADDIE model. The research method used in this research is the survey method. Data collection was carried out using observation, interviews, and document analysis. In this research, the data obtained is qualitative. The qualitative data was then analyzed descriptively. The analysis showed that Indonesian language teachers in three schools, SMA PGRI Lumajang, SMAN 1 Kunir, and SMA Muhammadiyah Lumajang need companion books in learning to write, especially on exposition texts. Students can use the companion teaching materials to practice writing exposition texts gradually with a good and structured process. The results showed that (1) the primary teaching materials used by teachers and students have not focused on writing skills, especially writing exposition texts, and (2) companion teaching materials are needed for learning to write exposition texts. This research is expected to be useful for teachers in teaching writing skills and for students. It can be a companion book to improve exposition text writing skills.